2007
DOI: 10.1002/hep.21702
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen–associated sequence polymorphisms in hepatitis C virus reveal reproducible immune responses and constraints on viral evolution†

Abstract: CD8 ؉ T cell responses play a key role in governing the outcome of hepatitis C virus (HCV) infection, and viral evolution enabling escape from these responses may contribute to the inability to resolve infection. To more comprehensively examine the extent of CD8 escape and adaptation of HCV to human leukocyte antigen (HLA) class I restricted immune pressures on a population level, we sequenced all non-structural proteins in a cohort of 70 chronic HCV genotype 1a-infected subjects (28 subjects with HCV monoinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 42 publications
7
101
0
1
Order By: Relevance
“…The HLA associations observed in that study are reproduced in the analysis performed here (using the Fisher's exact test for the entire dataset) but are not included as they fall above the stringent cutoff set in this study. Three sites shown in Tables 2 and 3 overlapped with HLA-associated viral polymorphisms identified by Timm et al 5 (NS3-1398, NS3-1444, NS5B-2841). In addition, three sites identified in the report by Timm et al were of borderline significance in our study (NS2-881, P ϭ 0.04; NS3-1019, P ϭ 0.07; NS5A-2153, P ϭ 0.02).…”
Section: Amino Acid Variation Within Published and Predicted Viral Epmentioning
confidence: 62%
See 3 more Smart Citations
“…The HLA associations observed in that study are reproduced in the analysis performed here (using the Fisher's exact test for the entire dataset) but are not included as they fall above the stringent cutoff set in this study. Three sites shown in Tables 2 and 3 overlapped with HLA-associated viral polymorphisms identified by Timm et al 5 (NS3-1398, NS3-1444, NS5B-2841). In addition, three sites identified in the report by Timm et al were of borderline significance in our study (NS2-881, P ϭ 0.04; NS3-1019, P ϭ 0.07; NS5A-2153, P ϭ 0.02).…”
Section: Amino Acid Variation Within Published and Predicted Viral Epmentioning
confidence: 62%
“…Viral polymorphisms within or flanking these epitopes can result in escape from HLA-restricted CTL responses, providing an effective mechanism for the virus to subvert host immune control (reviewed by Bowen and Walker 3 ). We and others 4,5 have shown that viral polymorphisms in the HCV genotype 1 genome are associated with specific HLA class I alleles, indicating adaptation of HCV to HLA-restricted immune pressure.…”
Section: H Epatitis C Virus (Hcv) Is a Genetically Diversementioning
confidence: 78%
See 2 more Smart Citations
“…Studies utilizing population-based genetic approaches, which examine the association between specific viral polymorphisms and the HLA types of individuals within a host population, have demonstrated viral escape (adaptation) to HLA-restricted immune pressure evident at the population level for both HIV and HCV (Gaudieri, Rauch et al 2006;Timm, Li et al 2007) . The approach is based on the premise that the host's HLA molecules regulate immune responses by presenting specific viral epitopes to T lymphocytes and viral polymorphisms within or flanking these epitopes that compromise the efficacy of these T lymphocyte responses (i.e.…”
Section: Hcv Diversity and Viral Adaptationmentioning
confidence: 99%